2017
DOI: 10.1177/0734282917732857
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Structure of the Wechsler Adult Intelligence Scale–Fourth Edition with an Egyptian Sample

Abstract: The Wechsler Adult Intelligence Scale–Fourth Edition (WAIS-IV) is one of the most well-known tests in the field of adult intelligence assessment. This study explores the validity of the Egyptian adaptation for the subscales of the WAIS-IV. Confirmatory factor analysis (CFA) indicated that the first-order, second-order, and bifactor models of both the five-factor Cattel–Horn–Carroll (CHC) and the four-factor structures fitted with the WAIS-IV. When the Arithmetic subscale was pathed to Perceptual Reasoning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Interestingly, the dimensionality results using the genetic algorithm indicated that the WAIS-IV subtests analyzed in this study are unidimensional except for Matrix Reasoning, Information, Similarities, and Vocabulary, which are multidimensional. The appearance of more than one scale for some of the WAIS-IV subtests using Mokken analysis may explain the findings of previous studies such as Abdelhamid et al (2019), Bowden et al (2011a), Weiss, Keith, Zhu, and Chen (2013a, 2013b), which suggested that some of these subtests were loaded on more than one factor. As such, the total score of each the WAIS-IV subtests (except multidimensional subtests) can be computed to determine the adult’s level on the latent trait being measured.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Interestingly, the dimensionality results using the genetic algorithm indicated that the WAIS-IV subtests analyzed in this study are unidimensional except for Matrix Reasoning, Information, Similarities, and Vocabulary, which are multidimensional. The appearance of more than one scale for some of the WAIS-IV subtests using Mokken analysis may explain the findings of previous studies such as Abdelhamid et al (2019), Bowden et al (2011a), Weiss, Keith, Zhu, and Chen (2013a, 2013b), which suggested that some of these subtests were loaded on more than one factor. As such, the total score of each the WAIS-IV subtests (except multidimensional subtests) can be computed to determine the adult’s level on the latent trait being measured.…”
Section: Discussionmentioning
confidence: 84%
“…The WAIS-IV Arabic version was used (Abdelhamid et al, 2019), which, like the English version, has 10 core subtests and five supplemental subtests that generate a score for four indices: VC, PR, WM, and PS. Some of these subtests are scored 0, 1 (e.g., dichotomous data).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations